Study of vital sign monitoring with textile sensors in swimming pool environment - Silva, Marcos (2009)
This paper presents the results of a series of experiments aiming at the optimisation of vital sign monitoring using textile electrodes to be used in a swimsuit. The swimsuit will integrate sensors for the measurement of several physiological and biomechanical signals; this paper will focus on ECG and respiratory movement analysis. The data obtained is mainly intended to provide tools for evaluation of high-performance swimmers, although applications can be derived for leisure sports and other situations. A comparison between electrodes based on different materials and structures, behaviour in dry and wet environments, as well as the behavior in different extension states, will be presented. The influence of movement on the signal quality, both by the muscular electrical signals as well as by the displacement of the electrodes, will be discussed. The final objective is the integration of the electrodes in the swimsuit by knitting them directly in the suit’s fabric in a seamless knitting machine